Wind Speed Distribution in Ninava Governorate - Waleed Al-Rijabo; Lamia fayik; Bashar Jaro (College of Education for Pure Sciences, 2009)
Abstract Wind speed was studied in four locations in Ninava Governorate which are Mosul, Rabea, Sinjar and Talafar for the period (1980-2002). The mean monthly values, the standard deviation, the coefficient of variation and the time series for the wind speeds was studied during this period in all locations. Wind power density and Weibull distribution were found in the different locations. The results were shown in tabulated and graphical form. The results indicate in Mosul, Rabea and Sinjar slightly downward trend in the time series of wind speed while in Talafar no trend was observed also a reasonable agreement was obtain between actual data of wind speed and that calculated by Weibull distribution.